Health Education and Promotion of Covid-19 Vaccine on the Willingness of Pregnant Women for Covid-19 Vaccination - Pakpahan, Sulastry (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Efforts to prevent Covid-19 by implementing various health protocols and the body's immune system are needed during pregnancy. Pregnant women are recommended to get the COVID-19 vaccine to protect pregnant women and their babies from infection with Covid-19. In Indonesia, the COVID-19 vaccine is given to pregnant women starting in the second trimester of pregnancy and the second dose is given according to the interval of the type of vaccine. Based on the initial survey where the Covid-19 vaccine coverage was still low for pregnant women for reasons such as fear of injections, lack of support from husbands and families, fear of being exposed to Covid-19 after vaccination. This study is a quantitative study with a pre-experimental design method of type one group pretest-posttest, to determine the effect of providing education and health promotion of Covid-19 vaccination to pregnant women on the willingness of pregnant women to be vaccinated against Covid-19. Sampling with stratified random and meet the inclusion criteria as many as 134 people. The instrument of data collection was done by using a questionnaire, the analysis using the Paired Sample T Test. the results of the t test were obtained t count > t table (p = 0.025; <0.05), so it was concluded that there was an effect of pregnant women's knowledge about the Covid-19 vaccine in pregnancy on the mother's willingness to participate in the Covid-19 vaccination. Efforts need to be made to increase the knowledge of pregnant women through health promotion education on Covid-19 vaccination by health workers to reduce the doubts of pregnant women in participating in the Covid-19 vaccination and increase the coverage of Covid-19 vaccination for pregnant women.